Effects of chronic cytochrome P-450 inhibition on the course of hypertension and end-organ damage in Ren-2 transgenic rats - Chábová, Vera Certíková; Kramer, Herbert J; Vanecková, Ivana; Vernerová, Zdena; Eis, Václav; Tesar, Vladimír; Skaroupková, Petra; Thumová, Monika; Schejbalová, Stanislava; Husková, Zuzana; Vanourková, Zdenka; Kolský, Alexander; et al. (Vascular pharmacology, 2007)
The aim of the present study was to evaluate the effects of inhibition of cytochrome P-450 (CYP) activity by 1-aminobenzotriazole (ABT) and by CoCl(2), first, on the development of hypertension when treatment was started in young male heterozygous Ren-2 transgenic rats (TGR) and, second, on blood pressure (BP) when treatment was started in adult TGR with established hypertension. Normotensive Hannover Sprague-Dawley (HanSD) rats served as controls. In addition, the renal cortical activities of omega-hydroxylase, the enzyme catalyzing the formation of 20-hydroxyeicosatetraenoic acid (20-HETE), and of epoxygenase, the enzyme responsible for epoxyeicosatrienoic acids (EETs) production, and urinary excretion of 20-HETE and EETs in TGR and HanSD rats were assessed. TGR have higher renal tissue omega-hydroxylase activity and urinary excretion of 20-HETE but have significantly lower renal epoxygenase activity and urinary excretion of EETs than HanSD rats. Treatment of young TGR with ABT and CoCl(2) attenuated the development of hypertension and cardiac hypertrophy and prevented glomerulosclerosis. Administration of ABT and CoCl(2) in adult TGR decreased BP, cardiac hypertrophy, but did not reduce glomerulosclerosis. Our data suggest that altered production and/or action of CYP-derived metabolites play a permissive role in the development and maintenance of hypertension in TGR by enhancing ANG II-induced vasoconstriction.
Keywords: náhodné rozdělení; Kidney Cortex; Oxygenases; Hydroxyeicosatetraenoic Acids; renin; Hypertension; kobalt; cytochrom P-450 CYP2J2; krysa rodu Rattus; Cobalt; zvířata; kůra ledviny; Triazoles; vazokonstrikce; oxygenasy; Cytochrome P-450 Enzyme Inhibitors; kardiomegalie; Glomerulosclerosis, Focal Segmental; Cytochrome P-450 CYP4A; Renin; Cardiomegaly; Cytochrome P-450 Enzyme System; kyseliny hydroxyeikosatetraenové; potkani Sprague-Dawley; krevní tlak; Male; hypertenze; Heterozygote; inhibitory enzymů; Rats; fokálně segmentální glomeruloskleróza; triazoly; Animals; heterozygot; Rats, Sprague-Dawley; inhibitory cytochromu P450; Renin-Angiotensin System; mužské pohlaví; Cytochrome P-450 CYP2J2; Vasoconstriction; Blood Pressure; Disease Models, Animal; Enzyme Inhibitors; renin-angiotensin systém; cytochrom P450 CYP4A; systém (enzymů) cytochromů P-450; Random Allocation; modely nemocí na zvířatech